Problems of linguistically gifted Arabic language learners speaking other languages - Aljohany, Abdulrahman Mohammed Saeed (Journal of Humanities & Social Sciences, 2021)
This study aims to identify the problems faces Linguistically-Superior Learners of Arabic and reveal the obstacles and challenges the teacher faces when teaching linguistically-superior learners. The researcher used the descriptive-analytical approach to achieve the study objectives, and the questionnaire was the study tool which applied to a sample of students of Arabic language institutes ​​in Saudi Arabia. The results of the study revealed a list of problems of linguistically-superior Arabic language learners related to the curriculum, the teacher and the learner himself. Based on the findings of the study, the researcher suggested a number of recommendations, the most prominent of which were: attention to Linguistically-Superior Learners of Arabic as a Foreign Language and provide them special needs and attention to the curricula of Linguistically-Superior Learners of Arabic as a Foreign Language.